Implementation of Video Feedback Within a Community Based Naturalistic Developmental Behavioral Intervention Program for Toddlers With ASD: Pilot Study - Klein, Claire B.; Swain, Deanna M.; Vibert, Bethany; Clark-Whitney, Elysha; Lemelman, Amy R.; Giordano, Jennifer A.; Winter, Jamie; Kim, So Hyun (Frontiers in Psychiatry, 2021)
Video feedback (VF) is an intervention delivery technique that complements naturalistic developmental behavioral interventions (NDBI) and parent-mediated interventions (PMI) by using caregiver-child interaction videos reviewed with a clinician to facilitate behavioral change in caregivers. Although VF has been implemented in PMI with young children with ASD, examinations of feasibility and acceptability, as well as the potential effectiveness of VF in community settings, have been limited. In this pilot randomized control trial (NCT03397719; https://clinicaltrials.gov/ct2/show/NCT03397719), families were randomized into a state-funded Early Intervention (EI) NDBI program or the NDBI program augmented with VF. Results demonstrated high levels of implementation and acceptability of VF augmenting the community-based EI program in caregivers and clinicians. Both groups showed significant improvements after 6 months in social communication symptoms and some areas of developmental and adaptive skills. Clinical Trial Registration:https://clinicaltrials.gov/ct2/show/NCT03397719, identifier: NCT03397719.